Melanopsin DNA aptamers can regulate input signals of mammalian circadian rhythms by altering the phase of the molecular clock - Nakazawa, Kazuo; Matsuo, Minako; Kikuchi, Yo; Nakajima, Yoshihiro; Numano, Rika (Frontiers in Neuroscience, 2024)
DNA aptamers can bind specifically to biomolecules to modify their function, potentially making them ideal oligonucleotide therapeutics. Herein, we screened for DNA aptamer of melanopsin (OPN4), a blue-light photopigment in the retina, which plays a key role using light signals to reset the phase of circadian rhythms in the central clock. Firstly, 15 DNA aptamers of melanopsin (Melapts) were identified following eight rounds of Cell-SELEX using cells expressing melanopsin on the cell membrane. Subsequent functional analysis of each Melapt was performed in a fibroblast cell line stably expressing both Period2:ELuc and melanopsin by determining the degree to which they reset the phase of mammalian circadian rhythms in response to blue-light stimulation. Period2 rhythmic expression over a 24-h period was monitored in Period2:ELuc stable cell line fibroblasts expressing melanopsin. At subjective dawn, four Melapts were observed to advance phase by >1.5 h, while seven Melapts delayed phase by >2 h. Some Melapts caused a phase shift of approximately 2 h, even in the absence of photostimulation, presumably because Melapts can only partially affect input signaling for phase shift. Additionally, some Melaps were able to induce phase shifts in Per1::luc transgenic (Tg) mice, suggesting that these DNA aptamers may have the capacity to affect melanopsin in vivo. In summary, Melapts can successfully regulate the input signal and shifting phase (both phase advance and phase delay) of mammalian circadian rhythms in vitro and in vivo.